AKTIVITAS ANTIBAKTERI DAN PENELUSURAN SENYAWA AKTIF EKSTRAK GASTROPODA YANG TERSEBAR DI KAWASAN KONSERVASI MANGROVE DAN BEKANTAN KOTA TARAKAN - Imra, Imra; Jaw, Novelianus; Abdiani, Ira Maya; Maulianawati, Diana (Universitas Teuku Umar, 2025)
Gastropods are a class within the phylum Mollusca that contain active compounds with potential antibacterial properties. Antibacterial are compounds that can inhibit growth and kill bacteria harmful to biota and humans. This study aimed to determine the active compounds and antibacterial activity in extracts of Cassidula spp., Cerithidea obtusa, Telescopium spp., Chicoreus spp., Cerithidea cingulata, Nerita spp. This study began with sampling, preparation, extration, and testing of active compounds consisiting of alkaloids, steroidas, flavonoids, saponins (from test), phenol hydroquinone, and tannins, as well as testing antibacterial activity. The results showed that the gastropod extracts exhibited antibacterial activity against Vibrio parahaemolyticus, as indicated by the inhibition zones: Chicoreus spp. (11 mm), Cerithidea obtusa (10 mm), and Cerithidea cingulata (11.5 mm), all categorized as strong; Cassidula spp. (5 mm) and Nerita spp. (6 mm), categorized as moderate; and Telescopium spp. (3 mm), categorized as weak. The active compounds detected in each type of gastropod were alkaloids, flavonoids, and phenol hydroquinones. In contrast, steroid compounds were only found in Telescopium spp. and Cassidula spp., while saponin were present in the extracts of Nerita spp., Cerithidea obtusa, Chicoreus spp., and Cerithidea cingulata.Keywords: Active compounds, Antibacterial, , Extraction , Gastropods